Sinergi Tata Kelola Zakat Antara Kantor Wilayah Kementerian Agama Provinsi Bengkulu dan Baznas Provinsi Bengkulu - Septy Veronica (JAKA: Jurnal Analisis Kebijakan Kementerian Agama, 2023)
ABSTRACT The purpose of this study is to describe the synergy of the implementation of zakat management and empowerment between the Regional Office of the Ministry of Religion of Bengkulu Province and BAZNAS of Bengkulu Province. Study uses a qualitative approach. The results of the study show that zakat is a mâliyah ijtima'iyah worship which has a very important, strategic and decisive position, both in terms of Islamic teachings and in terms of developing the welfare of the people. The Regional Office of the Ministry of Religion of Bengkulu Province has the responsibility to provide guidance in the field of zakat empowerment, including to zakat management institutions in Bengkulu Province as working partners. One of the zakat management institutions is BAZNAS Bengkulu Province. The form of synergy in zakat management is that UPZ Regional Office of the Ministry of Religion of Bengkulu Province has collected zakat, infaq and shadaqah funds from all Civil Servants (PNS) through a salary deduction system, held activities in collaboration with BAZNAS Bengkulu Province, held monitoring activities for zakat fund management at BAZNAS City Regency throughout Bengkulu Province, Guidance for Amil Zakat Bimtek, and provision of Provincial BAZNAS Operational assistance in accordance with the provisions and availability of funds every year. Keywords: synergy, zakat management